Chemical Composition of Essential Oil of Senecio vernalis Waldst. Et Kit. (Asteraceae) from Turkey - Bagci, Eyup; Kilic, Omer (Taylor & Francis Ltd, 2012)
The chemical composition of essential oil of Senecio vernalis (Asteraceae) from Turkey was analyzed by GC and GC-MS system. The yield of the oil is 0.4 ml. The essential oil composition of S. vernalis was studied and thirty nine components representing 91.5 % of the total oil were identified. The main constituents of S. vernalis were beta-phellandrene (12.6 %), 1,8-cineole (9.2 %), caryophyllene oxide (7.3 %), beta-selinene (6.3 %) and limonene (6.2 %). The chemical distribution of essential oil compounds in the genus pattern were discussed in means of chemotaxonomy and natural products.
Keywords: Senecio; Asteraceae; Essential oil; beta-phellandrene; 1,8-cineole